Perioperative exercise programmes to promote physical activity in the medium to long term: systematic review and qualitative research - Michael W Pritchard; Amy Robinson; Sharon R Lewis; Suse V Gibson; Antony Chuter; Robert Copeland; Euan Lawson; Andrew F Smith (Health and Social Care Delivery Research, 2022)
Background: In England, more than 4 million hospital admissions lead to surgery each year. The perioperative encounter (from initial presentation in primary care to postoperative return to function) offers potential for substantial health gains in the wider sense and over the longer term. Objectives: The aim was to identify, examine and set in context a range of interventions applied perioperatively to facilitate physical activity in the medium to long term. Data sources: The following databases were searched – Cochrane Central Register of Controlled Trials, MEDLINE, the Cumulative Index to Nursing and Allied Health Literature, EMBASE, PsycINFO and SPORTDiscus in October 2020. Clinical trials databases were also searched, and backward and forward citation searches were conducted. Review methods: We undertook a systematic review; ran database searches in October 2020; extracted data; conducted risk-of-bias assessments of studies; and used Grading of Recommendations Assessment, Development and Evaluation assessments. We conducted focus groups and interviews with people running services designed to promote physical activity, to understand the practical and contextual factors that make such interventions ‘work’. Although the two streams of work were conducted independently, we considered overlapping themes from their findings. Results: In the review, we found 51 randomised controlled trials and two quasi-randomised trials; nine non-randomised studies formed a supplementary data set. Studies included 8604 adults who had undergone (or were undergoing) surgery, and compared 67 interventions facilitating physical activity. Most interventions were started postoperatively and included multiple components, grouped as follows: education and advice, behavioural mechanisms and physical activity instruction. Outcomes were often measured using different tools; pooling of data was not always feasible. Compared with usual care, interventions may have slightly increased the amount of physical activity, engagement in physical activity and health-related quality of life at the study’s end (moderate-certainty evidence). We found low-certainty evidence of an increase in physical fitness and a reduction in pain, although effects generally favoured interventions. Few studies reported adherence and adverse events; certainty of these findings was very low. Although infrequently reported, participants generally provided positive feedback. For the case studies, we conducted two online focus groups and two individual interviews between November 2020 and January 2021, with nine participants from eight services of physical activity programmes. Conceptual and practical aspects included how the promotion of physical activity can be framed around the individual to recruit and retain patients; how services benefit from committed and compassionate staff; how enthusiasts, data collection and evidence play key roles; and how digital delivery could work as part of a blended approach, but inequalities in access must be considered. Limitations: Outcome measures in the review varied and, despite a large data set, not all studies could be pooled. This also limited the exploration of differences between interventions; components of interventions often overlapped between studies, and we could not always determine what ‘usual care’ involved. The case study exploration was limited by COVID-19 restrictions; we were unable to visit sites and observe practice, and the range of services in the focus groups was also limited. Conclusions: Evidence from the review indicates that interventions delivered in the perioperative setting, aimed at enhancing physical activity in the longer term, may have overall benefit. The qualitative analysis complemented these findings and indicated that interventions should be focused around the individual, delivered locally and compassionately, and promoted by a patient’s full clinical team. There is a need to develop a core outcome set for similar studies to allow quantitative synthesis. Future work should also investigate the experiences of patients in different contexts, such as different communities, and with different surgical indications. Study registration: This study is registered as PROSPERO CRD42019139008. Funding: This project was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme and will be published in full in Health and Social Care Delivery Research; Vol. 10, No. 21. See the NIHR Journals Library website for further project information.